Successful combination of endoscopic pyloromyotomy and balloon dilatation for hypertrophic pyloric stenosis in an older child: A novel procedure - Yokoyama, Satoshi (Surg Case Rep, 2016)
BACKGROUND: Hypertrophic pyloric stenosis (HPS) is a rare cause of gastric outlet obstruction beyond infancy. Ramstedt pyloromyotomy remains the gold standard treatment for HPS. This type of HPS can be managed successfully with pyloromyotomy under laparoscopic or open procedures. Endoscopic pyloric balloon dilation (EPBD) has not been recommended in the treatment of HPS, and there are only a small number of reported cases who had had successful endoscopic pyloromyotomy (EP) for HPS only in infants. CASE PRESENTATION: The patient was suspected of having HPS when the patient was 1 year old after infancy. However, his parents thought that the vomiting and poor sucking were caused by Down syndrome-associated muscular hypotonia. Since then, no additional tests have been performed at their request. At 6 years of age, he was readmitted to our department because of persistent vomiting and failure to thrive, and HPS was diagnosed again. However, it was unknown whether the HPS had been persisting since infancy or was acquired. The first EPBD was slightly effective but did not remain effective for a long time. When the second EPBD was performed in combination with EP, the amount and frequency of vomiting were reduced dramatically. CONCLUSIONS: The combination of EP and EPBD procedure may represent a safe, effective, and minimally invasive option for selected HPS patients in whom laparotomy would pose a significant risk or who do not respond to conventional medical treatment. To our knowledge, this is the first report to describe combination treatment with EP and EPBD in an older child with HPS.